Evaluation of the effectiveness of energy sustainability measures through the dynamic energy consumption model - Fortea, Costinela; Cristea, Dragos Sebastian; Zlati, Monica Laura; Antohi, Valentin Marian; Neculita, Mihaela; Cristache, Nicoleta; Lazarescu, Ioana (Frontiers in Energy Research, 2024)
The current context of economic development requires paying close attention to the energy industry. Since 2022, European countries has been facing specific problems due to energy crises against the background of the geopolitical conflict and the measures provided by European forums in order to reduce dependence on energy imports from Russia. In this context, we aim to define a new model of energy consumption and the function of energy sustainability at the European level, aspects that will lead to highlighting the position of the 27 European member states in the period 2005–2022 in terms of their energy sustainability. The methodology used is based on the study of literature, the consolidation of databases, econometric modelling, and procedures for testing the validity of modelling results. The results of the study are useful to European energy policy decision-makers in view of the necessary adjustments to achieve the objectives of the 2030 and 2050 Agenda.